Comparative Study on Customer Fulfillment Of E-Banking Facilities - et. al., Dhanya B K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With stiff competition and technological advances, the banking systems face challenges. For providers, it is important to satisfy consumers with the quality of the service anticipated by them. Therefore, the current study intended to recognize the client’s perception of a facility, both transaction-based and future technologies in government owned banks in terms of its comparative assessment. Likewise, through the current study, we would gauge the range of internet-enabled services (e-services) and e-banking services adoption in bank sector in this e-age. The aim of this study was to determine the extent of the usage of services in particular e-services, in all the banks and also to examine the constituent’s aspects influencing client fulfillment and the quality of service providers. Cronbach’s Alpha method was used to find validity of variables used in the questionnaire and internal consistency of scaled data. Total hundred items were checked by using Cronbach’s Alpha method. The respondents are selected by using purposive sampling method. The analysis indicates that customers of banking institutions were not happy with the workers behavior, accessibility and communication but satisfied with e-banking services